The Realization of Politeness Strategies in EFL Teacher-Students Classroom Interaction - Rahayuningsih, Dian; Saleh, Mursid; Fitriati, Sri Wuli (Universitas Negeri Semarang, 2020)
Politeness is one of the prominent issues in pragmatics. It becomes a major issue in education due to the implementation of curriculum 2013 which emphasized on character education. This study aimed at analyzing the realization of politeness strategies and sociological factors influencing the choice of politeness strategies in EFL Teacher-students classroom interaction at SMP Semesta Bilingual School. This study used qualitative research in the form of classroom discourse analysis. The participants were an EFL teacher and 30 EFL students in two EFL classrooms. The research instruments were made based on Brown and Levinson (1987) framework of politeness strategies. The findings showed that bald on record, positive politeness, negative politeness, and off records were realized in the classroom interaction. The teacher dominantly used positive politeness to show solidarity and to maintain a close relationship with the students, bald on records to give a clear and unambiguous instruction, negative politeness to minimize the coercion to the students, and off record to give hints. In addition, the sociological factors, namely distance, power, and degree of imposition influence the choice of politeness strategies. As the conclusion, politeness is important in maintaining relationship and creating a comfortable environment in EFL classroom.